2000
DOI: 10.1002/(sici)1096-9071(200004)60:4<387::aid-jmv4>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

TT virus infection in patients with chronic hepatitis B or C: Influence on clinical, histological and virological features

Abstract: Concomitant infection with TT virus and hepatitis B virus (HBV) or hepatitis C virus (HCV) is common. However, the effect of TTV infection on chronic hepatitis B or C is unknown. The prevalence of TTV infection, the effect of TTV infection on the clinical, histological and virological features of patients with chronic hepatitis B or C, and the influence of TTV infection on the HCV response to interferon alfa therapy were studied. A total of 100 asymptomatic hepatitis B surface antigen carriers, 220 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
1
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 28 publications
8
17
1
4
Order By: Relevance
“…The prevalence of TTV positivity in uremic patients has been found in different studies to range between 29.5% and 61%, which is much higher than the reported TTV prevalence among the normal population (1-12%) (16,18,20). Recently, Ikeuchi et al (21) investigated the frequency of superinfection with TTV and HCV (which is known to be endemic among hemodialysis patients), and reported no deleterious effect of TTV on HCV-induced chronic liver disease.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The prevalence of TTV positivity in uremic patients has been found in different studies to range between 29.5% and 61%, which is much higher than the reported TTV prevalence among the normal population (1-12%) (16,18,20). Recently, Ikeuchi et al (21) investigated the frequency of superinfection with TTV and HCV (which is known to be endemic among hemodialysis patients), and reported no deleterious effect of TTV on HCV-induced chronic liver disease.…”
Section: Discussionmentioning
confidence: 76%
“…In subsequent studies, it was shown that the virus did not have an important pathogenicity in TTV-positive healthy cases and in different subgroups. Concomitant infection with TTV and either hepatitis B virus (HBV) or HCV is common (18). However, the effect of TTV infection in cases of chronic hepatitis B or C infection is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TTV infection may be acquired during hemodialysis procedure or by nosocomial transmission. [6,19] However, a non-parenteral route of viral transmission, such as fecal-oral exposure [3] or maternal transmission, [4] has been suggested. TTV genome fragments have been detected in both sera and stool.…”
Section: Discussionmentioning
confidence: 99%
“…Serum was assayed for HCV RNA by reverse transcription-PCR with primers from the most conserved 5Ј untranslated region of the viral genome, and identification of the HCV genotype was done with type-specific primers as described previously (9). To avoid false-positive results, the methods described by Kwok and Higuchi (11) to prevent cross contamination were applied.…”
Section: Methodsmentioning
confidence: 99%